Brain MRI activity during the year before pregnancy can predict post-partum clinical relapses. (December 2021) - Lehmann, Hillel; Zveik, Omri; Levin, Netta; Brill, Livnat; Imbar, Tal; Vaknin-Dembinsky, Adi
Background: There are fewer multiple sclerosis (MS) relapses during pregnancy, although relapse risk increases in the early post-partum period, as has been predicted by pre-pregnancy or pregnancy disease activity in some studies. Objective: The aim of this study was to evaluate the correlation between magnetic resonance imaging (MRI) changes in the year before pregnancy and the relapse rate in the year post-partum. Methods: An observational retrospective case–control study included 172 pregnancies in 118 females with MS. Statistical analyses were used to evaluate the correlation between MRI and post-partum relapses. Clustered logistic regression was used to investigate the predictors of early post-partum relapses. Results: We found a significant correlation for an active-MRI pre-pregnancy and relapses in the first 3 months post-partum ( p < 0.001). Expanded Disability Status Scale (EDSS) pre-pregnancy and relapses in the first 3 months post-partum were also significantly correlated ( p = 0.009). Using a multivariate model, we predicted which women will not experience post-partum relapse by EDSS and by an active-MRI pre-pregnancy (96.7% specificity; p < 0.001). Conclusion: An active-MRI pre-pregnancy is a strong and sensitive predictor of early post-partum relapse, regardless of whether the woman had clinical evidence of disease activity prior to conception and delivery. This finding could provide clinicians with a strategy to minimize post-partum relapse risk in women with MS planning pregnancy.